Multicenter Study of Outcomes with Ceftazidime-Avibactam in Patients with Carbapenem-Resistant Enterobacteriaceae Infections - King, Madeline (Antimicrob Agents Chemother, 2017)
Ceftazidime-avibactam is a novel cephalosporin–beta-lactamase inhibitor combination that is active against many carbapenem-resistant Enterobacteriaceae (CRE). We describe a retrospective chart review for 60 patients who received ceftazidime-avibactam for a CRE infection. In-hospital mortality was 32%, 53% of patients had microbiological cure, and 65% had clinical success. In this severely ill population with CRE infections, ceftazidime-avibactam was an appropriate option.